Three-Point Bending Behavior of 3D-Printed Tough-PLA Lattice Beams: Effects of Lattice Topology and Beam Width - Yasin Kuddusi Kutucu; Muhammet Muaz Yalçın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study investigates the fabrication of single and double-row lattice beams utilizing three distinct lattice structures: cubic, octet, and body-centered cubic (BCC), using Tough-PLA filament. This material exhibits similar plastic deformation characteristics to traditional PLA filament but possesses superior strength. Mechanical properties of the bulk Tough-PLA filament were evaluated through standard tensile testing. Subsequently, to assess the influence of lattice configuration and beam width, the single and double-row beams were subjected to three-point bending tests. The experimental data were analyzed in terms of specific energy absorption, crush force efficiency, and specific force value, allowing for comparisons with existing literature to identify the most effective parameters. The findings indicate that the octet lattice structure, featuring angled struts, is the most efficient design as beam thickness increases. Conversely, for single-row beams with narrower widths, the BCC lattice—with both vertical and angled struts—emerges as the optimal design. Additionally, cubic lattices consistently displayed the least favorable performance due to their reliance on vertical struts across all beam widths examined.